(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The given article illustrates data about structural foundation of Mass media terms in the English and Uzbek languages. Through the analysis isomorphic and allomorphic features of Mass media terms in terms of structure have been identified in order to compare and contrast above mentioned languages. Terms were analyzed according to their components.